(untitled) (Alternautas, 2022)
ere I attempt to think about the insertion of a recent theoretical-political field and diverse and branching development—that of Latin American Political Ecology—into a plural framework with very specific characteristics—the tradition of Latin American critical thinking. A first version of this obsession was recently published (Alimonda, 2015). Perhaps it would be redundant to clarify that I do not intend to sketch an itinerary in the open field of formal history of ideas in Latin America, among what has been thought and written in this corner of the world. Instead, I attempt to identify Latin American ideas as a critical, perhaps one could say ontological, reflection about its own existence. We will be delimiting diffuse pathways in a very steep and foggy territory, full of spectres, among which the new passengers will choose their ancestors or kill the dead, as Derrida said (1994: 119)